Magneto-dynamic method in wireless transmission of electrical energy - Pedro Osvaldo Díaz Fustier; Orestes Hernandez Areu; Josnier Ramos Guardarrama (Revista Científica de Ingeniería Energética)
Wireless transmission of electrical energy was born at the beginning of the 20th century, but at commercial level it is relatively recent in recharging of mobile phone batteries and in electric vehicles (first decade of the 21st century), using the development of contemporary electronics, both authors working with synchronous generators note that there is a wireless transmission with certain advantages, this text presents experiments based on the mechanical rotation of stationary magnetic fields (magneto-dynamic method) very similar to the excitation in synchronous generators , there were some first tests in a British university in 2014 as the only reference of previous use. Experimenting on this topic has no historical precedents in Cuba, but any scientific achievement on the topic is highly valued because they are paths not usually used, being a fertile field for future research that could obtain potentially interesting results developed from laboratory experiments carried out.